Compressive neuropathy in the upper limb - Mukund R Thatte; Khushnuma A Mansukhani (Indian Journal of Plastic Surgery)
Entrampment neuropathy or compression neuropathy is a fairly common problem in the upper limb. Carpal tunnel syndrome is the commonest, followed by Cubital tunnel compression or Ulnar Neuropathy at Elbow. There are rarer entities like supinator syndrome and pronator syndrome affecting the Radial and Median nerves respectively. This article seeks to review comprehensively the pathophysiology, Anatomy and treatment of these conditions in a way that is intended for the practicing Hand Surgeon as well as postgraduates in training. It is generally a rewarding exercise to treat these conditions because they generally do well after corrective surgery. Diagnostic guidelines, treatment protocols and surgical technique has been discussed.